Growth and spectroscopy of orthorombic Yb:KY(MoO4)2 laser crystal with a layered structure. (December 2019) - Volokitina, A; Loiko, P; Serres, J M; Mateos, X; Kuleshov, N; Trifonov, V; Pavlyuk, A
Abstract: We report on the growth, structure, vibronic and spectroscopic properties of novel Yb 3 +-doped orthorhombic potassium yttrium double molybdate crystal, Yb:KY(MoO4 )2 . The layered structure of this material determines a strong polarization-anisotropy of absorption and emission bands of Yb 3 + ions. The maximum stimulated-emission cross-section is 3.7×10 -20 cm 2 at ∼1.01 μm for light polarization E ∥ b and the lifetime of the 2 F5/2 state is 0.46 ms. Naturally cleaved Yb:KY(MoO4 )2 plates are suitable for microchip lasers at ∼1 μm.